A Review on Big Data Architecture and It`s Application for Future Aspect - Saha, Srinjoy; Nej, Sneha; Saha, Rupa; Ghosh, Debmitra; Rauth, Anal (International Journal of Computer Sciences and Engineering, 2026)
This increase in data is not going to slow down anytime soon. Data too large or complex for traditional database systems can be ingested, processed, and analyzed using a big data architecture. Depending on the capabilities of a company's users and tools, the threshold for entering into the big data realm may differ. This paper is mainly focuses on essential questions for Big Data Architecture – What is Big Data Architecture, Big Data Architecture Layers, Types of Big Data Architecture, Big Data Architecture Application, Benefits of Big Data Architecture and Big Data Architecture Challenge